Applying Numerical Methods to Differential Equations for Wildlife Conservation Strategies - Venkateswara raju KONDURU; J. Kavitha; Dr. S. Gayathri; Dr. K. RAJAM; Dr. M. Musthafa Ibrahim; Dr. D. Rajinigirinath (The Bioscan, 2024)
Wildlife conservation strategies increasingly rely on mathematical modeling to understand and predict population dynamics. This paper highlights the crucial role of numerical methods in solving differential equations commonly used in these models. We discuss essential numerical methods, including Euler's method, Runge-Kutta methods, and adaptive methods, emphasizing their applications in modeling population growth, predator-prey interactions, disease spread, and habitat fragmentation. Through a case study on the impact of habitat loss on a bird population, we illustrate the practical application of these methods. We also address the challenges and limitations associated with numerical methods, emphasizing the importance of careful model selection, parameter estimation, and result interpretation. This paper underscores the significance of numerical methods as powerful tools for developing effective wildlife conservation strategies.